Circadian variation in sports performance - Atkinson, G.; Reilly, T. (Sports Medicine, 1996)
Chronobiology is the science concerned with investigations of time-dependent changes in physiological variables. Circadian rhythms refer to variations that recur every 24 hours. Many physiological circadian rhythms at rest are endogenously controlled, and persist when an individual is isolated from environmental fluctuations. Unlike physiological variables, human performance cannot be monitored continuously in order to describe circadian rhythmicity. Experimental studies of the effect of circadian rhythms on performance need to be carefully designed in order to control for serial fatigue effects and to minimise disturbances in sleep. The detection of rhythmicity in performance variables is also highly influenced by the degree of test-retest repeatability of the measuring equipment. The majority of components of sports performance, e.g. flexibility, muscle strength, short term high power output, vary with time of day in a sinusoidal manner and peak in the early evening close to the daily maximum in body temperature. Psychological tests of short term memory, heart rate-based tests of physical fitness, and prolonged submaximal exercise performance carried out in hot conditions show peak times in the morning. Heart rate-based tests of work capacity appear to peak in the morning because the heart rate responses to exercise are minimal at this time of day. Post-lunch declines are evident with performance variables such as muscle strength, especially if measured frequently enough and sequentially within a 24-hour period to cause fatigue in individuals. More research work is needed to ascertain whether performance in tasks demanding fine motor control varies with time of day. Metabolic and respiratory rhythms are flattened when exercise becomes strenuous whilst the body temperature rhythm persists during maximal exercise. Higher work-rates are selected spontaneously in the early evening. At present, it is not known whether time of day influences the responses of a set training regimen (one in which the training stimulus does not vary with time of day) for endurance, strength, or the learning of motor skills. The normal circadian rhythms can be desynchronised following a flight across several time zones or a transfer to nocturnal work shifts. Although athletes show all the symptoms of 'jet lag' (increased fatigue, disturbed sleep and circadian rhythms), more research work is needed to identify the effects of transmeridian travel on the actual performances of elite sports competitors. Such investigations would need to be chronobiological, i.e. monitor performance at several times on several post-flight days, and take into account direction of travel, time of day of competition and the various performance components involved in a particular sport. Shiftwork interferes with participation in competitive sport, although there may be greater opportunities for shiftworkers to train in the hours of daylight for individual sports such as cycling and swimming. Studies should be conducted to ascertain whether shiftwork-mediated rhythm disturbances affect sports performance. Individual differences in performance rhythms are small but significant. Circadian rhythms are larger in amplitude in physically fit individuals than sedentary individuals. Athletes over 50 years of age tend to be higher in 'morningness', habitually scheduling relatively more training in the morning and selecting relatively higher work-rates during exercise compared with young athletes. These differences should be recognised by practitioners concerned with organising the habitual regimens of athletes.